Sosialisasi Pembuatan Pupuk Organik dari Kotoran Sapi oleh Tim KKN UNS di Desa Srimulyo - Henry Yustanto; Astrid Widia Arningsih; Ahmad Ghaiyyas Afsaruddin; Bunga Azahra Kistar; Ilham Farras Pudiarna; Nadia Nur Afidah; Naila Khansa Aufa Yusman; Noor Hani Putranti; Rizal Arya Prayuda; Sahrul Sugma Jati; Tabhita Zahra Madanie (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2025)
The socialization of making organic fertilizer from cow dung by the Sebelas Maret University (UNS) KKN Team was carried out in Srimulyo Village, Gondang District, Sragen Regency, on 21 August 2024, with the aim of increasing awareness of farmers and breeders about the importance of organic fertilizer and offering environmentally friendly agricultural solutions. The partners for this activity are local communities, especially farmers and livestock breeders. Through socialization and direct demonstration methods, the KKN team introduced a simple method of processing cow dung into organic fertilizer. This activity not only emphasizes the benefits of organic fertilizer in increasing soil fertility, but also encourages reducing dependence on chemical fertilizers. The implementation of this activity received a positive response from the community, with the results showing an improvement in soil quality after using organic fertilizer. It is hoped that the impact of this activity can support the sustainability of organic farming in Srimulyo Village. In conclusion, this outreach activity succeeded in providing a new understanding for the community regarding the management of livestock manure as organic fertilizer and has great potential for further development.